Beyond Internationalization: Lessons from Post-Development - Beck, Kumari (Journal of International Students, 2021)
Despite the critiques generated in critical internationalization studies in response to the neoliberal and neocolonial orientation of internationalization of higher education, the direction of internationalization appears to be unchanged. This paper takes up the challenge of imagining internationalization otherwise by drawing from the field of post-development (PD) studies, which, it is argued, has parallels to the realities and debates on internationalization. An overview of the debates in PD and why they offer important ideas for critical internationalization studies will be followed by a discussion of how key analyses and arguments in PD can be applied to internationalization. This argument leads to the question of whether it is time to recognize an emerging post-internationalization movement, acknowledging that internationalization as we know it is in decline.